Cholesterol is Inefficiently Converted to Cholesteryl Esters in the Blood of Cardiovascular Disease Patients - Gerl, Mathias J. (2018)
We thank the nursing staff at the Hospital Santa Cruz, in particular Edite Tomas Mateus and Manuel Belo Costa for their enthusiastic involvement in this project and help in blood collection. This work was supported by iNOVA4Health - UID/Multi/04462/2013, a program financially supported by FCT (Foundation for Science and Technology of the Portuguese Ministry of Science and Higher Education) through national funds and co-funded by FEDER under the PT2020 Partnership, and Programas de Atividades Conjuntas (PAC) (Ref. No 03/SAICT/2015). ND is a holder of PhD fellowship from the FCT (Ref. No: SFRH/BD/51877/2012).